On Family Relationships under the Laws of Hammurabi - K. V. Karpenko (Vestnik MGIMO-Universiteta)
The article presents an analysis of the family relationships in ancient Babylon, in accordance with the laws of Hammurabi. The author dwells upon the characteristics of selected institutes of family law of the Amorites and comes to the conclusion that the family life in ancient Mesopotamia was very developped. The family in the Hammurabi Code represents the basis not only for economic and financial power of the state, but also for its political stability and security. The rights and obligations of spouses are not equal, but they are together, though each in his own way, achieving the main goal of the marital union - the birth and upbringing of children.